Critical Enzymatic Functions of FTO in Obesity and Cancer - Deng, Xiaolan; Su, Rui; Stanford, Savanna; Chen, Jianjun (Frontiers in Endocrinology, 2018)
Fat mass and obesity-associated protein (FTO) single-nucleotide polymorphisms (SNPs) have been linked to increased body mass and obesity in humans by genome-wide association studies (GWAS) since 2007. Although some recent studies suggest that the obesity-related SNPs in FTO influence obesity susceptibility likely through altering the expression of the adjacent genes such as IRX3 and RPGRIP1L, rather than FTO itself, a solid link between the SNP risk genotype and the increased FTO expression in both human blood cells and fibroblasts has been reported. Moreover, multiple lines of evidence have demonstrated that FTO does play a critical role in the regulation of fat mass, adipogenesis, and body weight. Epidemiology studies also showed a strong association of FTO SNPs and overweight/obesity with increased risk of various types of cancers. As the first identified messenger RNA (mRNA) N6-methyladenosine (m6A) demethylase, FTO has been shown recently to play m6A-dependent roles in adipogenesis and tumorigenesis (especially in the development of leukemia and glioblastoma (GBM)). Given the critical roles of FTO in cancers, the development of selective and effective inhibitors targeting FTO holds potential to treat cancers. This mini review discusses the roles and underlying molecular mechanisms of FTO in both obesity and cancers, and also summarizes recent advances in the development of FTO inhibitors.